A visão do Barão de Mauá sobre a política externa brasileira no Rio da Prata 1850-1865 - Ramos, Rui Mateus (2009)
This paper search to understand the vision of Baron of Maua about the Brazilian foreign policy in Plate River during the period from 1850 to 1865. From this correspondence used to Uruguay s diplomats Andre Lamas and Juan Jose Herrera, the paper also analyze the participation of Maua in the diplomatics relations between Brazil and the platinum countries. The used sources were written in a troubled historical context, marked by its civil wars in Uruguay, diplomatic conflict and tense performance of Brazilian diplomacy. Irineu Evangelista de Sousa, Baron and Viscount Maua, had and important participation in the politic events in Plate River between 1850 and 1865 and their wrote help to understand the complex diplomatic relationships between Brazil, Uruguay and Argentina. Along of there historic period, the interests of Maua in the Plate will be compatible with the extern politic developed by Brazilian government in the region. In a first moment, the present paper analyzes the reasons that caused the initial approximation between Maua and the Brazilian diplomatic in the 1850s. After that, is made the analyze of the written documentation by Maua in the 1860s, where are contained his criticals to Brazilian policy government to the Plata.